The application of a simplified model to assess the fairness of employee selection measures in a sample of white and coloured apprentices - X. C. Birkenbach; A. Allan (South African Journal of Business Management, 1988)
While the topic of fairness in personnel selection decisions has received a great deal of attention in the United States of America over the last two decades or so, little work has been done in South Africa in this regard. In view of the possible industrial relations implications of discrimination linked to test unfairness, research needs to be undertaken in this country to examine predictor-criterion relationships for the various race groups who make up the labour force. In the present study, a simplified approach for evaluating test fairness developed by Lawshe (1983) was tested in a sample of white and coloured apprentices. Four selection instruments were related to three criteria of job success. The results of the research seem to verify the results of studies conducted in America, namely, that little evidence has emerged supporting the concepts of differential validity and differential prediction of tests for different race groups. Future research should include samples consisting of black employees in order to compare their test and criterion profiles with those of persons from other racial groups.
Keywords: 650